Tinjauan Yuridis terhadap Tindak Pidana Pungutan Liar (Pungli) - I Wayan Arsa Yogi Wiguna; I Nyoman Sujana; I Nyoman Gde Sugiartha (Jurnal Preferensi Hukum, 2020)
In the community, it is often heard about illegal fees which are a form of criminal act. This study aims to determine the regulation of illegal levies (Pungli) based on Regional Regulation No. 8/2010 concerning levies, creations and sports and to determine the imposition of criminal sanctions against perpetrators who commit illegal extortion (Pungli). The research method used is the normative research method, primary and secondary legal material sources, records of statutory books and other literature are carried out to collect data, and analysis of legal materials using legal arguments. The results of this study indicate that the regulation of corruption is implied in the formulation of corruption in several articles including Article 423 of the Criminal Code referred to in Article 12 of Law Number 31 Year 1999 as a criminal act of corruption, which is then reformulated in Law Number. 20 of 2001 concerning the crime of corruption. Legal sanctions against extortion consist of social sanctions and criminal sanctions. The law on corruption is stated in it regarding the crime of extortion.